Factors Affecting Self-Regulation of Students in Indonesian Traditional Muslim Schools - Agus Fawait; Safaruddin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This study aims at identifying the factors affecting students' self-regulation. It is seen from Gender, Age, and Duration of study in the Islamic Boarding Schools, Formal Education, Parental Education, Previous Education, and Students Place of Origin. It is to find a new format for the self-regulation of students in traditional Muslim schools. This study applies a quantitative approach to identify factors or variables that influence learning based on student self-regulation. The research design uses an instrument to explore and identify variables. This research is sample research with the Proportional Random Sampling Cluster technique. This technique is used because the population has elements that are not homogeneous and structured proportionally This study uses a sample of 108 students with different backgrounds. From the results of the analysis, it was found that out of the seven factors proposed as variables, five factors influence the self-regulation of students. The findings of this study provide evidence that the student's background dimensions can significantly influence students' self-regulation, so the better the student's background, the better the student's self-regulation. We recommend further studies for deeper examination and analysis of these factors.